High Performance Computing and Applications Second International Conference, HPCA 2009, Shanghai, China, August 10-12, 2009, Revised Selected Papers - Zhang, Wu; Chen, Zhangxin; Douglas, Craig C.; Tong, Weiqin (Theoretical Computer Science and General Issues,, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on High Performance Computing and Applications, HPCA 2009, held in Shangahi, China, in August 2009. The 71 revised papers presented together with 10 invited presentations were carefully selected from 324 submissions. The papers cover topics such as numerical algorithms and solutions; high performance and grid computing; novel approaches to high performance computing; massive data storage and processsing; and hardware acceleration.